2014
DOI: 10.1038/ncomms4379
|View full text |Cite
|
Sign up to set email alerts
|

Female song is widespread and ancestral in songbirds

Abstract: Bird song has historically been considered an almost exclusively male trait, an observation fundamental to the formulation of Darwin's theory of sexual selection. Like other male ornaments, song is used by male songbirds to attract females and compete with rivals. Thus, bird song has become a textbook example of the power of sexual selection to lead to extreme neurological and behavioural sex differences. Here we present an extensive survey and ancestral state reconstruction of female song across songbirds sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
294
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 357 publications
(308 citation statements)
references
References 36 publications
9
294
1
4
Order By: Relevance
“…Song production by both sexes is thought to be ancestral (Odom et al 2014), and female song is more common in tropical species (Slater and Mann 2004). Most females possess complex call repertoires; the female Streak-backed Oriole (Icterus pustulatus) sings more than the male (Price et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Song production by both sexes is thought to be ancestral (Odom et al 2014), and female song is more common in tropical species (Slater and Mann 2004). Most females possess complex call repertoires; the female Streak-backed Oriole (Icterus pustulatus) sings more than the male (Price et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…(4) Both sexes should vocalize away from the nest to reduce predation risk from nest conspicuousness. (5) At artificial nests at which we broadcast female song, we predict higher egg predation when there is a higher rate of song. Prediction (1) could predict either a low song rate at later stages or (4) that both sexes will sing away from the nest.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is growing focus on the occurrence [3] and functions of female song [4], mostly using the perspective of life history and social selection theory. Female song is widespread and ancestral in songbirds, and females sing across 71% of extant species spanning 32 families [5]. Many Southern Hemisphere songbirds are sedentary, and females and their pair males sing solo song year-round to defend the territory [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Much recent work has corrected this bias and found that while male song is certainly more common in some geographical regions, female song is widespread among songbirds (Odom et al, 2014) and can have important functions in many (if not all) of the same contexts as male song: defense of a territory, mate attraction, maintenance of the pair bond, and mate guarding (Hall, 2004;Slater and Mann, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to understanding the functions of female song, researchers are interested in the evolutionary history, and ecological correlates of female song (Price, 2009;Odom et al, 2014). Observers have long noted that female song is more common in tropical and sub-tropical areas than it is in temperate regions (Slater and Mann, 2004).…”
Section: Introductionmentioning
confidence: 99%